Landscape Design: Drawing a Planting Plan - Gail Hansen (EDIS)
Selecting and placing plants in the landscape is the art and science of arranging plant material to make a healthy, functional, and beautiful yard. The mix of science and art is expressed in the guiding principle of “right plant, right place,” meaning to select plants that can thrive in the growing conditions of the site and locating them for both visual appeal and health. Selecting and arranging plants are the last steps in the overall design process after the site analysis is complete and the activity areas located and designed. Developing the planting plan is a sequential process, but it is important to remember that the process is not completely linear; sometimes decisions about plant material require reworking previous steps in the sequence and making adjustments to the plan. This 10-page fact sheet was written by Gail Hansen and published by the UF Department of Environmental Horticulture, January 2012.